Physical activity promotion and health-enhancing physical activity education policy in EU healthcare: a cross-sectional survey of 27 member states - Romeu Mendes; Stephen Whiting; Callum Leese (BMJ Open)
Objectives Analyse data collected through the WHO Regional Office for Europe to describe the proportion of European Union (EU) member states that have relevant policies related to physical activity (PA) counselling and exercise referral schemes in healthcare settings and the education of health professionals in health-enhancing PA (HEPA).Design Cross-sectional survey.Setting and participants An online survey (LimeSurvey) was sent to nominated government representatives of the 27 EU member states (via the EU PA Focal Point Network) in March 2021. The survey was open for 2 months, with support offered to all national representatives by the WHO Regional Office for Europe throughout. The survey had been developed by a panel of experts and was previously disseminated (and analysed) in 2015 and 2018.Outcomes measures National recommendations regarding (1) PA counselling in healthcare settings and (2) the inclusion of HEPA within teaching curricula.Results All 27 countries responded. Of the 18 countries that reported national policies to provide PA counselling by healthcare professionals (HCPs), all reported that counselling on PA was provided through primary care, with an additional half also reporting PA counselling provision as part of secondary care. Twenty-one countries reported that HEPA is taught in the curricula of HCPs, but large variations exist regarding which cadres of HCPs have HEPA integrated within their curricula and whether the HEPA teaching is a mandatory or optional component of training.Conclusions Despite PA counselling being a key recommendation for promoting PA at the population level, only two-thirds of EU member states have national policies in place. Although three-quarters of EU member states report healthcare education curricula, including HEPA, more research is required to understand the methods and content of delivery and the subsequent effectiveness on knowledge and clinical outcomes.